ANALISIS PENGARUH FAKTOR FUNDAMENTAL DAN MAKRO EKONOMI TERHADAP RETURN SAHAM (Studi Kasus Pada Indsutri Makanan Dan Minuman yang Terdaftar di Bursa Efek Indonesia periode 2011-2015) - Ramli, Chairul Aly (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The population of this research is Food and Beverage Sector Companies listed on the Indonesia Stock Exchange period 2011 - 2013 as many as 14 companies. Sampling technique used was purposive sampling and obtained a sample of 11 companies. Variables used in this study were, Stock Return as the dependent variable and the Current Ratio, Debt to Equity Ratio, Return On Asset, Total Assets Turnover, exchange rate, inflation and interest rates SBI as an independent variable. The analysis technique used is multiple linear regression analysis with a significance level of 0.05.The results of regression analysis using partial test (t-test) showed that the variables Current Ratio, Debt to Equity Ratio, Return on Assets, Total Assets Turnover, exchange rate, inflation rates has no effect on stock returns of food and beverage sector. While the SBI rate have significant negative effect on stock return of food and beverage sector. From the results of the regression analysis of the results obtained simultaneously with a significance level of 0.05 (5%) of independent variables influence on stock returns.